2013
DOI: 10.1016/j.enbuild.2013.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent multi-agent system for building heat distribution control with combined gas boilers and ground source heat pump

Abstract: Intelligent energy system refers to the use of intelligent control strategies with the energy system, which can help minimise energy waste and loss, optimise load control, increase and improve energy efficiency and/or maximise the benefits of renewable energy. Renewable energy and intelligent controls are interlinked and correlated with each other. Without intelligent controls, the full benefits of renewable energy technologies may not be achievable, specifically the Ground Source Heat Pump (GSHP) technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Simulations results showed that 3% increase in overall comfort level and approximately 9% of the total energy was saved. Mokhtar et al (2013) proposed an ARTMAP multiagent BMS system. ARTMAP is a type of ANN that provides incremental learning inspired by how human processes memory and learns new information without necessarily forgetting the previously learned information (Carpenter et al 1991).…”
Section: Mas Applicationsmentioning
confidence: 99%
“…Simulations results showed that 3% increase in overall comfort level and approximately 9% of the total energy was saved. Mokhtar et al (2013) proposed an ARTMAP multiagent BMS system. ARTMAP is a type of ANN that provides incremental learning inspired by how human processes memory and learns new information without necessarily forgetting the previously learned information (Carpenter et al 1991).…”
Section: Mas Applicationsmentioning
confidence: 99%
“…Smart and energyefficient building are also the focus of some MAS applications [117], such as building heat distribution control [118]. A multiagent home automation system for power management was idealized by Abras et al [119] and is an interesting guideline for this kind of MAS application.…”
Section: Microgrid Demand Controlmentioning
confidence: 99%
“…Summarizing, while currently proposed systems demonstrate promising results in energy reduction and comfort preservation, most of them have been assessed only through simulations 2,11,[13][14][15]17,18,[20][21][22][23][24][26][27][28][31][32][33] that do not fully embody the complexities of a real-life commercial or tertiary building, even if real life building data were used as input for the simulations (eg, Agarwal et al 31 ). Moreover, some of the real-case applications are very limited in terms of deployment (eg, Goyal et al 5 ) and cannot be easily assessed in full.…”
Section: Novelty Statementmentioning
confidence: 99%